1999
DOI: 10.1002/(sici)1097-4628(19990321)71:12<1933::aid-app1>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Merrifield resin and 1,6-hexanediol diacrylate-crosslinked polystyrene resin for solid-phase peptide synthesis: A comparative study

Abstract: Three short peptides were synthesized on Merrifield resin (PS-DVB) and on polystyrene crosslinked with 1,6-hexanediol diacrylate resin (PS-HDODA) to compare their efficiencies in solid-phase peptide synthesis (SPPS). A 2% crosslinked polymeric system having almost equal capacity was used in both cases. The peptides were synthesized using standard solid-phase methodology. In the case of the PS-HDODA resin, all the couplings were completed by the first coupling and the peptides were obtained in Ͼ 90% yield and Ͼ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Merrifield resins are well known for their ability to facilitate solid phase peptide synthesis (SPPS). [11][12][13] Through a series of protection and deprotection steps, peptides with desired sequences can be formed using chromatography-free, facile purification techniques, e.g., filtration. Following this model, solid phase organic synthesis (SPOS), has been gaining popularity and expanding with the development of functional resins that possess similar reactivity to their non-supported counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Merrifield resins are well known for their ability to facilitate solid phase peptide synthesis (SPPS). [11][12][13] Through a series of protection and deprotection steps, peptides with desired sequences can be formed using chromatography-free, facile purification techniques, e.g., filtration. Following this model, solid phase organic synthesis (SPOS), has been gaining popularity and expanding with the development of functional resins that possess similar reactivity to their non-supported counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic studies of polymer supports in solid phase synthesis have shown that the flexible polymer supports enhance the reactivity of bound functional groups due to high solvation and smooth diffusion of soluble reagents throughout the polymer matrix. HDODA crosslinked polystyrene resin had been reported as an effective support in solid phase peptide syntheses27, 28 and polymeric reagents 29. In the preparation of polymeric ketones, under the same conditions, a twofold increase in the degree of functionalisation was observed in HDODA–PS resin when compared with the DVB–PS resin.…”
Section: Resultsmentioning
confidence: 99%
“…An efficient polymeric support for peptide synthesis should have optimum hydrophobic-hydrophilic balance compatible with the peptide being synthesized. Systematic studies on the polymersupported reactions show that the use of a flexible polymer support enhances the reactivity [2]. But the design and development of polymer supports having appropriate hydrophobic-hydrophilic balance is a difficult task.…”
Section: Methods Of Peptide Synthesismentioning
confidence: 99%